Biochemical Markers of Subclinical Atherosclerosis in Patients with Type 2 Diabetes Mellitus - Caridad Osorio Sosa; Leonar Luis Nápoles Acosta; Alfredo Salvador Vallés Gamboa; Alberto Caballero Laguna (Universidad de las Ciencias Médicas de Cienfuegos, 2022)
Background: insulin resistance and associated metabolic alterations, such as dyslipidemia, hypertension, obesity and hypercoagulability, influence the increasingly premature appearance and severity of atherosclerosis that patients with diabetes mellitus develop. Objective: to evaluate the biochemical markers of subclinical atherosclerosis in patients with type 2 diabetes mellitus. Method: a descriptive and cross-sectional study was carried out to evaluate biochemical markers of subclinical atherosclerosis in 100 patients with type 2 diabetes mellitus treated at the Guillermo Dominguez López General Teaching Hospital from April 2020 to March 2021. The used variables were: age, sex, blood pressure, personal medical history of diabetes mellitus, toxic habits and cardiovascular risk. These patients were classified according to their global cardiovascular risk using the risk charts established by the World Health Organization for the Americas region and total cholesterol, triglycerides, LDL cholesterol, HDL cholesterol, creatinine, uric acid determinations were performed, cystatin C, fibrinogen, high-sensitivity C-reactive protein. The information was processed using descriptive statistics methods, mainly rates and percentages. Results: most of the patients were classified in global cardiovascular risk 2 and 3. Their markers showed association with the risk categories established in each patient. The determinations of triglycerides, HDL-cholesterol and uric acid were the most significant to identify vascular damage in patients with type 2 diabetes mellitus. Conclusions: there was a direct relationship between altered values of high-sensitivity C-reactive protein and global cardiovascular risk in the studied patients.